Genomic Characterization of Selected Escherichia coli Strains from Catfish (Clarias gariepinus) in Nigeria - Chibuzo Linda Ekwuazi; Frank C. Ogbo; Anna Stöger; Werner Ruppitsch; Adriana Cabal Rosel (Applied Microbiology)
According to a report by the World Health Organization (WHO), each year, over 550 million individuals worldwide suffer from and 230,000 die from diarrheal illnesses, which accounts for more than half of the global foodborne disease burden. Among them, children face a heightened vulnerability, with approximately 220 million falling ill and 96,000 succumbing to these diseases annually. This work aimed to study the genomic characterization of selected E. coli strains from catfish (Clarias (C.) gariepinus) caught from the Onitsha North axis of the River Niger in Anambra state, Nigeria. A total of 50 fish were randomly purchased from different fishermen over a period of four months. Samples that comprised six different organs (skin, flesh, gills, gonads, guts, and liver) were screened for E. coli strains using cultural and biochemical methods. Multilocus sequence typing (MLST) and core genome (cg)MLST were performed using Ridom SeqSphere+ software. The aerobic plate count (APC) and coliform count ranged from 0.5 × 104 to 3.7 × 104 cfu/g and 0 to 3.0 × 104 cfu/g, respectively. Whole-genome sequencing (WGS) confirmed the presence of E. coli and Klebsiella quasipneumoniae isolates in our samples. We could identify only two serotypes (O102:H7 and O40:H4) of E. coli. Antimicrobial resistance genes (ARGs) and point mutations that conferred antibiotic resistance were extracted from the genome assemblies. Good hygiene is recommended to avoid the cross-contamination of raw C. gariepinus with ready-to-eat food.